Comparative Assessment of Antioxidant Properties Between In-Vitro Cultured Cat's Whiskers Leaves (Orthosiphon stamineus) and Quercetin - Fahrauk Faramayuda; Dinda Choirunnisa; Yenni Karlina (Green Engineering Society, 2025)
The present study investigates the antioxidant properties of in-vitro cultured leaves of cat's whiskers (Orthosiphon stamineus) compared to the well-known antioxidant quercetin. Antioxidants are crucial for neutralizing free radicals and play a significant role in protecting cells from oxidative stress, a contributing factor to various diseases and aging processes. The research aims to quantify and compare the radical scavenging activity of extracts from the in vitro cultured leaves and quercetin, using the DPPH method, a widely recognized assay in antioxidant research. Extraction involved macerating in-vitro cultured cat's whiskers leaves with 96% ethanol, which facilitates the dissolution of active phytochemicals. Antioxidant activity was subsequently assessed through the DPPH assay, where colorimetric change indicates the extract’s scavenging ability towards free radicals. The findings revealed that the in vitro cultured leaves extract exhibited a potent antioxidant activity, with an IC50 value of 0.74 μg/mL, significantly lower than quercetin’s IC50 value of 7.51 μg/mL. These results highlight the potential of in-vitro cultured cat's whiskers as a natural antioxidant source, suggesting possible applications in the food and pharmaceutical industries, where combating oxidative stress is essential for health maintenance and disease prevention. Further research is necessary to elucidate the specific biochemical pathways and mechanisms underpinning the antioxidant capacity of the in vitro cultured leaves extracts.